Feasibility and perceived benefits of a loyalty programme for a coffee shop in the Northern suburbs of Cape Town. - Augustyn, Susan (The IIE, 2022)
In recent years customers have shifted from perceiving loyalty programmes as an added benefit to a required customer service. Given the costly nature of loyalty programmes and the ongoing debate surrounding its effectiveness, it is important to know what types of benefits are perceived as valuable to the customer, while still being feasible to a small coffee shop. Consequently, the researcher set out to gain insights from customers concerning their perception of loyalty programme benefits. The benefits were grouped into utilitarian, hedonic and symbolic benefits, and customers’ perception for each respective group was investigated. The researcher chose in-depth interviews to collect data due to its supportive nature towards an interpretivist approach as well as qualitative research. Generation Z and Millennials were interviewed, and the semi-structured questionnaires allowed the researcher to discover the underlining motivations behind customers’ perceptions towards loyalty programme benefits. The most notable finding is customers’ disregard for benefits when hygiene factors (as per Herzberg’s theory) are not present at the coffee shop and that a loyalty programme alone is not able to change customers’ perception.
Keywords: Loyalty programmes; Consumer behaviour; Buying patterns; Brand loyalty